Ultrasound Diagnosis of a Twin Pregnancy Combining A Molar Pregnancy and A Normal Singleton Pregnancy About A Case in Bouake - YAO, Dr Brou Lambert; KOUAKOU, Dr. Kouassi Victorien; Paul Bonfils, Dr KOUASSI Kouamé; Baudoiun BRAVO-Tsri, Akoli Eklou; TANOH, Dr Kesse Emile; KOUADIO, Dr Allou Florent; KOUAKOU, Dr Bouassa Davy Mélaine; SANOGO, Dr Sara Carole; SORO, Dr Malick; KONATE, Pr Issa (Clinical Medicine And Health Research Journal, 2024)
Twin pregnancy combining a complete mole and a normal singleton pregnancy with its own healthy trophoblast is a rare entity. The most formidable complication is the progression towards gestational trophoblastic disease. We report the case of a 29-year-old patient, primigravida, consulting for metrorrhagia with amenorrhea of ​​approximately 12 weeks. The pelvic ultrasound performed revealed the association of a complete hydatidiform mole and a normal singleton pregnancy. A medical termination of the pregnancy was decided with first expulsion of a fetus with its trophoblast followed by expulsion of multiple vesicles of different sizes. The evolution is marked by the decline of plasma BHCG until negativation after 10 weeks.